PENGARUH DESAIN PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA UKM DINA KELURAHAN NTOBO - Haryanti, Intisari sari; Ismunandar, Ismunandar; Kurniati, Eka (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2024)
The purpose of this research is to determine the decisions of Dina SME consumers in making purchases. UKM Dina is a UKM that produces quality woven fabric so that UKM Dina has great potential to develop further and be known by the wider community. The increasing interest of local people and tourists in woven fabrics is one of the reasons that encourages craftsmen at UKM Dina to create the latest designs from woven fabrics while maintaining the authenticity of the techniques and motifs. This research uses associative research using quantitative data from primary data sources, namely data obtained directly from respondents' questionnaire answers to the research object. The research instrument used in this research was a Likert scale questionnaire. The population used in this research is all SME Dina consumers in the city of Bima, the exact number of which is unknown (unknown population), the sample size is 50 people. The data collection techniques used were observation, questionnaires and literature review. The data analysis techniques used are validity test, reliability test, classic assumption test (normality test, multicollinearity test, autocorrelation test, heteroscedasticity test), multiple linear regression analysis, multiple correlation coefficient, decision test, f test, and t test. The research results show that only product design has a significant influence on purchasing decisions, while UKM Dina's brand image has no effect.